Online interventions and virtual day centres for young people who use drugs: potential for harm reduction? - Matej Sande; Bojan Dekleva; Špela Razpotnik; Darja Tadič; Mija Marija Klemenčič Rozman; Jana Rapuš Pavel (BMC, 2023)
Abstract Background The methodological part of the large-scale study on the psychosocial distress of young people in Slovenia focused on vulnerable young people who use drugs and explored the potential of online interventions in harm reduction programmes. We looked at the needs of young people who, at the time of the research, were attending a virtual Discord day centre hosted by the DrogArt NGO or were involved in the organisation's other programmes. We explored young people's knowledge of online interventions, their satisfaction with them and the opportunities they offer for harm reduction programmes. Methods The study used a qualitative methodology with a combination of deductive and inductive coding, and relied on framework analysis, 18 young people who had used drugs or had stopped using participated in the study. The inclusion criterion was a maximum age of 25 years. In-depth interviews were conducted with the young people, which lasted on average between one and a half and two hours. Results The study showed the potential of online interventions, specifically the virtual day centre, which provide a safe and relaxed space for young people in the sample to meet and talk, which is accessible and where they feel welcome. Online interventions have also enabled some of the sample to engage in the 'offline' support types offered within the organisation. The main advantages of online interventions are seen by young people as being more 'geographically' accessible and more available during the COVID-19 epidemic. Online support suits some people because they can leave sessions more quickly and it is more informal, while others prefer it because of specific problems or difficulties, such as social anxiety. Conclusions The results show the relatively high potential of online interventions in harm reduction programmes, as well as more broadly for young people with various psychosocial difficulties and who, for example, do not use drugs. These types of support allow quick contact with a professional or peer and facilitate contact with a support programme. Young people are still poorly informed about the support programmes available in Slovenia and would like more information. Thus, in addition to developing and upgrading the network of programmes, we need to focus on providing information to young people through channels that are close to them and can reach them.